Project-Based Learning and Biopreneurship for Developing Students’ Systems Thinking: A Literature Review - Anjani, Aprilia Ika Dewi; Jufri, A. Wahab; Artayasa, I Putu; Doyan, Aris (Current Educational Review, 2025)
Systems thinking is one of the most important abilities in the 21st century. Systems thinking helps students organize their thoughts in a meaningful way and make connections between seemingly unrelated problems to reveal their interrelatedness. Through systems thinking, learners are directed to first recognize a problem, understand the links between the factors causing the problem, and finally find the right solution and prevent new problems from arising. Systems thinking skills can be facilitated through learning with an integrated biopreneurship Project-Based Learning (PjBL) model. This study aims to identify how the positive trends of research on biopreneurship and systems thinking variables. This research method is descriptive and analytical. The data used in this study were obtained from documents indexed by Google Scholar from 2016 to 2025 using Publish or Perish and Dimension.ai. The data identified and analyzed were the type of publication, the source of publication, and the title of the research on the project-based learning (PjBL) model integrated with biopreneurship to improve students' systems thinking skills. The data analysis method uses text analysis assisted by VOS viewer software. The results of the study show that the research trend of the biopreneurship PjBL model to improve system thinking skills is very low from 2016-2025. In the period 2016 to 2019, no publications were recorded. Entering 2020 and 2021, the number of publications began to appear, with one publication per year each. However, in 2022, there was a drastic decline to zero, indicating that there were no publications that met the criteria. A positive trend was again seen in 2023 with one publication, and the peak occurred in 2024, where two publications were recorded, being the highest number in the observed period